Joule heating scanning structure system - Moya, Javier Alberto (2016)
A method and its system to study the structural evolution on soft magnetic amorphous and nanocrystalline ribbon shaped alloys are presented. With only one sample, a complete set of magnetic and electric data at room and at high temperature are obtained in a relatively short period of time, allowing us to elucidate the structural changes occurring in the alloy and to determine the optimal soft magnetic properties annealing conditions.